Computational modelling and analysis of impeded and unimpeded taxi-out time at congested airports - Hoo, Xuan Tao (Nanyang Technological University, 2023)
In this study, a Deep Reinforcement Learning (DRL) approach is proposed to optimize the pre-departure sequencing of aircraft at airports, with the objective of minimizing taxi delays and queuing time. The research focuses on two main components: synthetic schedule generation and agent pre-training with supervised learning.